The Problem of Cognitive Dissonance at the Lexical-Semantic Level in Literary Work - Qobilova Nargisa Sulaymonbekovna; Ibragimova Gulshan Raimovna (Genius Journals, 2022)
This article contains a number of theories in translation studies aimedat determining lexical-semantic features, sorting translations, and enriched with modern theories over time. This article gives a comparative analysis of scholarly works and their translations, one of the foremost critical issues nowadays. The phenomenon of cognitive dissonance, which occurs within the translation of works, is additionally discussed about in this article
Keywords: Theory Of Cognitive Dissonance; Literary Translation; Lexical-Semantic Features; Writer